Transcriptome and proteome dynamics in chemostat culture reveal how Campylobacter jejuni modulates metabolism, stress responses and virulence factors upon changes in oxygen availability. (2nd October 2017) - Guccione, Edward J.; Kendall, John J.; Hitchcock, Andrew; Garg, Nitanshu; White, Michael A.; Mulholland, Francis; Poole, Robert K.; Kelly, David J.
Summary: Campylobacter jejuni, the most frequent cause of food‐borne bacterial gastroenteritis worldwide, is a microaerophile that has to survive high environmental oxygen tensions, adapt to oxygen limitation in the intestine and resist host oxidative attack. Here, oxygen‐dependent changes in C . jejuni physiology were studied at constant growth rate using carbon (serine)‐limited continuous chemostat cultures. We show that a perceived aerobiosis scale can be calibrated by the acetate excretion flux, which becomes zero when metabolism is fully aerobic (100% aerobiosis). Transcriptome changes in a downshift experiment from 150% to 40% aerobiosis revealed many novel oxygen‐regulated genes and highlighted re‐modelling of the electron transport chains. A label‐free proteomic analysis showed that at 40% aerobiosis, many proteins involved in host colonisation (e.g., PorA, CadF, FlpA, CjkT) became more abundant. PorA abundance increased steeply below 100% aerobiosis. In contrast, several citric‐acid cycle enzymes, the peptide transporter CstA, PEB1 aspartate/glutamate transporter, LutABC lactate dehydrogenase and PutA proline dehydrogenase became more abundant with increasing aerobiosis. We also observed a co‐ordinated response of oxidative stress protection enzymes and Fe‐S cluster biogenesis proteins above 100% aerobiosis. Our approaches reveal key virulence factors that respond to restricted oxygen availability and specific transporters and catabolic pathways activated with increasing aerobiosis.